a)
x-y = -1,5
2x + y = -1
x = y -1,5
2(y-1,5) + y = -1
x = y-1,5
2y -3 + y = -1
x = y-1,5
3y = 2
x = y-1,5
y = 2/3
x = 2/3 - 3/2
y = 2/3
x = -5/6
y = 2/3
b)
(2x + y)/(3+y) = 4
x + 3y = 8
2x + y = 12 + 4y
x + 3y = 8
x = (12-3y)/2
(12-3y)/2 + 3y = 8
x = (12-3y)/2
12-3y + 6y = 16
x = (12-3y)/2
3y = 4
x = (12-3y)/2
y = 4/3
x = 4
y = 4/3
c)
x/2 + 3y/5 = 7/2
x -2y = -9
5x + 6y = 35
x -2y = -9
x = (35-6y)/5
(35-6y)/5 - 2y = -9
x = (35-6y)/5
35-6y -10y = -45
x = (35-6y)/5
-16y = -80
x = (35-6y)/5
y = 5
x = 1
y = 5